دراسة وتقييم تأثير تعدد البيئات على أداء الشبكات اللاسلكية IEEE802.11 من حيث الإنتاجية والتأخير - أحمد أحمد صقر; محمد عفراء (Latakia University Journal -Engineering Sciences Series, 2018)
With the tremendous development in the field of technology and communications, the need for the possibility of exchanging information and access to the Internet in any place and time, this has led researchers to develop networks and move to the field of wireless networks, which is the standard IEEE 802.11 as its representative. The aim of this study is to evaluate the performance of WLANs defined by the standard IEEE 802.11 in terms of throughput and delay which are the most important metrics that determine the performance and effectiveness of any network. The study was carried out using the OPNET 14.5 simulator and conducting many experiments and comparing them in terms of throughput and delay. The results generally show that 802.11g gives similar values ​​at different data rates, while the rest of the standards and when the data rate increases, the throughput increases and the delay decreases. As the number of nodes increases, throughput and delay increase. Enhanced Distributed Coordination Function (EDCF) gives good results to support requirements of Quality of Service (QoS). The results also showed that the application of the fragmentation threshold and Request to Send (RTS) improves network performance at a specific limit, while increasing Buffer Size increases delays and reduces throughput. دراسة وتقييم تأثير تعدد البيئات على أداء الشبكات اللاسلكية IEEE802.11 من حيث الإنتاجية والتأخير مع التطور الهائل في مجال التكنولوجيا والاتصالات، والحاجة إلى إمكانية تبادل المعلومات والوصول إلى الانترنت في أي مكان و زمان، هذا الأمر قد دفع الباحثين إلى تطوير الشبكات والانتقال إلى مجال الشبكات اللاسلكية، والتي يعد المعيار IEEE 802.11 ممثلاً لها. إن هدف هذا البحث هو تقييم أداء الشبكات المحلية اللاسلكية المحددة بالمعيار IEEE 802.11 من ناحيتي الإنتاجية و التأخير، كونهما من أهم المعايير التي تحدد أداء و فعالية أي شبكة. تمت الدراسة باستخدام المحاكي OPNET 14.5 و القيام بالعديد من التجارب، و مقارنتها من ناحية الإنتاجية و التأخير. أظهرت النتائج بشكل عام أن المعيار 802.11g يعطي قيم متشابهة عند معدلات النقل المختلفة، بينما باقي المعايير و عند زيادة معدل نقل البيانات، تزداد الإنتاجية و يقل التأخير. أما عند زيادة عدد العقد تزداد الإنتاجية و التأخير. كما أن تابع التنسيق الموزع المحسن EDCF (Enhanced Distributed Coordination Function) يقدم نتائج جيدة من أجل دعم متطلبات جودة الخدمةQoS (Quality of Service) ، و كذلك أظهرت النتائج أن تطبيق عتبة التجزئة و عتبة طلب الإرسال (Request To Send) RTS عند حد معين، تحسن من أداء الشبكة، أما زيادة حجمBuffer Size يزيد من التأخير و يقلل الإنتاجية.